Effectiveness of chloroform-softened gutta percha master cone in the apical seal of endodontically treated teeth in comparison with a master cone with an apical third tugback - Bautista, Ma. Emilyn M.; Maliwanag, Dennisa Ellen B.; Dominguez, Lisa (Adviser).; Porter, Irene (Adviser).
Ninety central incisors were tested in vitro to determine if varying the amount of chloroform used in the formed cone gutta percha filling technique has an effect on the apical seal.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gutta percha; Endodontics